The goods and services tax (GST) on takāful products: a critical Sharīʿah appraisal - Burhanuddin Lukman; Saba' Radwan Jamal Elatrash (ISRA International Journal of Islamic Finance, 2017)
Purpose: This paper aims to ascertain the Sharīʿah (Islamic law) stance on the imposition of goods and services tax (GST) on tabarruʿ-based takāful (donation-based Islamic insurance) products in Malaysia. The paper aims to do so by analysing the philosophy, Purpose:s and structure of GST on takāful products and comparing the imposition of GST on tabarruʿ-based takāful with its imposition on conventional insurance while probing into the Sharīʿah texts and opinions of classical and contemporary scholars about taxation in Islam. Design/methodology/approach The paper uses a qualitative research methodology. In addition to the literature and text on websites, the information on how GST is applied in practice is also obtained through interviews, discussions and documents from takāful operators. To determine the Sharīʿah position on GST, reference has been made to classical and contemporary Sharīʿah literature, including local and international Sharīʿah advisory bodies' resolutions and standards. Findings This study finds that a strict interpretation of Sharīʿah does not allow for the imposition of GST; however, there is still room for the government to justify it using a broader interpretation of maṣlaḥah (public interest). Takāful has become a need for the society and is subscribed to by all income groups, and not only by the rich. Hence, the government should consider exempting takāful products from GST. The basis of tabarruʿ in takāful does not provide conclusive Sharīʿah evidence for takāful to be exempted from GST. Originality/value This research paves the way for the industry to propose further measures on GST for takāful products such as the exemption of GST on the tabarruʿ amount or imposition of a zero rate of GST on the relevant takāful fees and charges that are currently burdensome to consumers.
Keywords: 330; GST; insurance; Sharīʿah; tabarruʿ; takāful